Investigation of Heavy Metals Level in selected Boreholes around the Vicinity of some Cemeteries in Benin City, Nigeria - C.A.E. Ibhadode; I.R. Ilaboya (Journal of Applied Sciences and Environmental Management, 2021)
Groundwater pollution by heavy metals such as lead, copper, nickel and iron is one of the major environmental issues of concern which has developed into a widely studied area. In this study, attempt was made to investigate the level of heavy metals in selected boreholes around the vicinity of cemeteries in Benin City. Seventy-two (72) samples of groundwater were taken from boreholes in 9 stations around the three cemeteries in Benin City on monthly basis. The samples were analysed for 7 heavy metals, in accordance with standard procedures. The heavy metals include; Zinc, Lead Iron, Copper, Cadmium, Nickel and Mercury. From the results of the study, a variation in the mean concentration of zinc was observed. The mean concentration of zinc in site 1 was 0.450mg/l, for site 2, it was 0.140mg/l and for site 3, it was 1.0533mg/l. For iron, mean concentration was 0.072mg/l in site 1. For site 2, mean concentration of iron was 2.140mg/l and for site 3, mean concentration of iron was 0.560mg/l. It was further revealed based on the results that mean value of heavy metals in groundwater around cemeteries in Benin City were generally lower during dry season compared to wet season. In addition, result of computed pollution index (Pi) revealed that the heavy metal with the highest potential to pollute groundwater is Cadmium, with Pi of 0.5333 and 0.400 representing dry season and wet season respectively.